PENENTUAN AUDIT FEE DITINJAU DARI KOMPLEKSITAS PERUSAHAAN, INTERNAL AUDIT DAN RISIKO AUDIT - Meithy Yusica; Wiwit Apit Sulistyowati (Universitas Muhammadiyah Malang, 2020)
The audit fee is in return for a fee paid by the client entity for a public accountant based on a contractual agreement on providing audit services. This research aims was to analyse the influence of the company's complexity, internal audit and audit risk partially against the audit fee in manufacturing companies of consumer goods industry listed on the Indonesia Stock Exchange for the period 2014 to 2018. The selection of samples on this study was conducted using purposive sampling methods and obtained 80 samples. Multiple linear regression analysis was used in this research. The results of this study showed that a partially complexity of the company has positive effect on the audit fee, internal audit has negative affect on the audit fee and audit risk using both current ratio measurement and dummy variable loss no effect on the audit fee.